Sosialisasi dan Pelatihan Pembuatan Deodoran Spray Untuk Mendorong Kewirausahaan Kosmetik Skala Rumah Tangga - Aditya Nuryanto Saputra; Irfan Ahsani; Jaka Seprianto Lepangkari; Aria Sanjaya; Elia Azani; Edi Sutarmanto (JURPIKAT, 2026)
Community service activities is a one of the Tridharma of Higher Education to realize cooperation with the community. Stikes Ar-Rum and Delik Village Regional Government collaborated to provide knowledge focused on the use of herbal compounds that can be used as natural ingredients for making deodorant.participants learned about skin health and the use of natural compounds that have antibacterial potential, one of it is alum. Participants also taught direct practice in making deodorants, starting from material preparation to product packaging. Through this service activity, the community is expected to be able to produce high-quality herbal deodorant spray and have new enterpreneuer opportunities that can give a new industry and UMKM.